Pengembangan Ekonomi Hijau Melalui Praktek Daur Ulang Sampah Organik menjadi Kompos di Desa Lumahan Kecamatan Senyerang, Kabupaten Tanjung Jabung Barat - Umiyati, Etik; Hastuti, Dwi; Parmadi; Zevaya, Faradina; Prihanto, Purwaka Hari (WIDA Publishing, 2024)
The development of a green economy through organic waste recycling practices into compost in Lumahan Village, Senyerang Sub-district, Tanjung Jabung Barat Regency, represents a strategic step in supporting the concept of sustainable and environmentally friendly economic growth. This program aims to process organic waste into valuable compost while raising public awareness about the importance of sustainable waste management. In addition to providing positive environmental impacts by reducing the volume of waste disposed of in landfills, this activity also creates new economic opportunities through the sale of compost. The program involves various stakeholders, including farmers and village officials, to encourage the integration of recycling practices into daily life. The program is expected to increase the amount of organic waste processed into compost, reduce the volume of waste ending up in landfills, and enhance community welfare through compost sales. Furthermore, this program is anticipated to serve as a model for other villages in implementing sustainable waste management systems and supporting the transition toward a green economy.